Numerical Simulation Strategy Optimization Analysis of Submarine Resistance and Flow Field - LI Peng, WANG Chao, SUN Huawei, GUO Chunyu (Shanghai Jiaotong Daxue xuebao, 2022)
In order to explore the influence of different turbulence models on the resistance and flow field of an advancing submarine, based on the STAR-CCM+platform, and taking Sub-off as the geometric model, this paper adopts the finite volume method, combing 10 turbulence models to conduct numerical research on hydrodynamic and flow field characteristics of Sub-off. First, the LES-Smagorinsky turbulence model is used for the convergence of grids and time steps. Then, the appropriate grid and time step are selected to calculate 10 kinds of turbulence models in specific cases. Finally, the selected turbulence model is used to analyze the hydrodynamic characteristics and flow fields of Sub-off. The results show that there are great differences among the 10 turbulence models in the prediction of submarine hydrodynamic performance and flow field characteristics. LES-Smagorinsky can not only predict the hydrodynamic performance and the average flow field of submarine, but also accurately predict secondary variables of flow fields.